2018
DOI: 10.17221/179/2017-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial potential of artichoke (Cynara scolymus L.) extract in beef patties

Abstract: The antioxidant and antimicrobial potential of artichoke extract (AE) in raw beef patties (RBPs) was evaluated during the storage. The RBPs were prepared with the addition of 500 and 1000 ppm AE. Also, Escherichia coli ATCC25922 and Listeria monocytogenes ATCC19118 were inoculated to each RBP to follow the antimicrobial activity. An evaluation of the instrumental colour, pH, total phenolic content (TPC), 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity, TBARS and microbiological properties was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
(33 reference statements)
2
10
0
Order By: Relevance
“…By progress of storage time at 4 ± 1 °C, both of TPC and antioxidant activity significantly decreased in all samples from the five treatments (T1-T5). These results agreed with those obtained by Ergezer et al (2018) who reported a significant decrease in TPC and antioxidant activity during the cold storage of artichoke extract containing beef patties. Also, Nassar et al (2016) reported a similar decrease in beef burgers incorporated with orange peel powder, pomegranate peel powder or tomato pomace powder by progress of the storage time.…”
Section: Total Phenolic Content Antioxidant Activity and Tbars Of Beef Burgerssupporting
confidence: 93%
See 3 more Smart Citations
“…By progress of storage time at 4 ± 1 °C, both of TPC and antioxidant activity significantly decreased in all samples from the five treatments (T1-T5). These results agreed with those obtained by Ergezer et al (2018) who reported a significant decrease in TPC and antioxidant activity during the cold storage of artichoke extract containing beef patties. Also, Nassar et al (2016) reported a similar decrease in beef burgers incorporated with orange peel powder, pomegranate peel powder or tomato pomace powder by progress of the storage time.…”
Section: Total Phenolic Content Antioxidant Activity and Tbars Of Beef Burgerssupporting
confidence: 93%
“…However, the results showed a high positive correlation between the addition level of MPE and both of TPC (r = 0.961) and antioxidant activity (r = 0.924) of stored beef burgers. These results agree with those reported in beef burgers and patties (Abdeldaiem and Ali, 2012;Nassar et al, 2016 andErgezer et al, 2018). Further, Nor Adilah et al ( 2018) observed an increase in TPC and free radicals scavenging activities of fish gelatin films at (3-5%) addition level of mango peel extract.…”
Section: Total Phenolic Content Antioxidant Activity and Tbars Of Beef Burgerssupporting
confidence: 89%
See 2 more Smart Citations
“…4 In literature, the liver-protective properties, anticarcinogenic effects and cholesterol-lowering effects of artichokes were presented. 5 It has also been reported that artichoke is a good source of antioxidants due to the significant amount of caffeic acid it contains. It is known that caffeic acid derivatives are the main phenolic substances found in the heart of artichokes.…”
Section: Introductionmentioning
confidence: 99%